Evaluation of tomato, spinach and carrot based vegetable Soy Soup - Verma, Tarun; Singh, Jai; Singh, Sabhajit Prasad (Vegetable Science, 2012)
Soup and beverages are generally consumed by large number of people for its being tasty and nutritious. The use of pure vegetable soup or fruit juice as breakfast drink has grown dramatically in recent year. Tomato (Solanum lycopersicum) contains lycopene (the red pigement in tomato), vitamin A, C, potassium and iron and nicotinic acid. Consumption of tomato everyday helps in improving skin texture, colour and various types of cancers, protects the liver from cirrhosis, dissolve gallstones, natural antiseptic, prevent heart diseases and good blood purifier (Nutrition and recipes, 2008). Spinach (Chenopodiaceae) is an excellent source of Vitamin A, B2, B6, C, K, E, manganese, foliate, magnesium, iron, calcium, potassium, dietary fiber, copper, protein, phosphorus and zinc. In addition it also has Omega-3 fatty acids, niacin and selenium. Spinach (Palak) contains lutein which is protective against eye diseases. Spinach is said to be good for those with heart disease, arthritis